LPS-induced extracellular AREG triggers macrophage pyroptosis through the EGFR/TLR4 signaling pathway - Yuan, Gang; Qiao, Qudi; Jiang, Aolin; Jiang, Zehui; Luo, Haihua; Huang, Lin; Wang, Jieyan; Jiang, Yong (Frontiers in Immunology, 2025)
Amphiregulin (AREG), a member of the EGF family, exists as a transmembrane protein anchored to the cell surface. In response to external stimuli, its extracellular domain is released into the extracellular matrix through paracrine or autocrine signaling. However, its role in septic macrophage pyroptosis remains poorly understood. This study aims to investigate the role of extracellular AREG in septic macrophages, mice, and patients. We found that high expression of extracellular AREG was regulated by RPLP1 at the translation level, which increased the expression of IL-6, CCL2, and CCL3 protein, as well as Caspase 1, IL-1β, and Nlrp3 mRNA expression, resulting in macrophage pyroptosis. Mechanistically, macrophage pyroptosis was aggravated by extracellular AREG pretreatment, which was triggered by extracellular AREG and ATP (adenosine 5′-triphosphate). The AREG-neutralizing antibody reduced LPS-induced epidermal growth factor receptor (EGFR) activation, TLR4 expression, and pyroptosis. Extracellular AREG-induced macrophage pyroptosis decreased with EGFR and NF-κB inhibition, as well as TLR4 and Myd88 knockout. Additionally, DTT-pretreated extracellular AREG suppressed macrophage pyroptosis. In vivo, extracellular AREG attenuates systemic inflammation infiltration and delays survival in a septic mouse model. Furthermore, extracellular AREG mediates sepsis in humans, and genes involved in the AREG-mediated pyroptosis signaling pathway were highly expressed in patients with severe sepsis compared with those with general or moderate sepsis. Overall, LPS-induced extracellular AREG aggravated or triggered macrophage pyroptosis through the EGFR/TLR4/Myd88/NF-κB signaling pathway, providing promising treatment strategies for sepsis.